2022
DOI: 10.1364/oe.461866
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of catastrophic optical mirror damage in continuous-wave high-power laser diodes using multi-section waveguides

Abstract: One of the persistent obstacles for high-power laser diodes (LDs) has been the catastrophic optical mirror damage (COMD), which limits the operating power level and lifetime of commercial high-power LDs. The output facet of LD reaches a critical temperature resulting in COMD, which is an irreversible device failure. Here, we fabricate multi-section LDs by tailoring the waveguide structure along the cavity that separates the output facet from the heat-generating lasing region. In this method, the LD waveguide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…This study uses a multi-section waveguide method shown in Figure 1 to effectively separate laser heat load from the output facet, hence strongly reducing facet temperature even below the laser cavity temperature developed in our previous work [19,20]. In this work, we fabricated and carried out detailed characterization of the devices, studied their optimum working conditions, and revealed the elimination of COMD in LDs [21,22]. The LD waveguide is divided into two sections, laser and passive waveguide, which gives electrical and thermal isolation.…”
Section: Design and Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses a multi-section waveguide method shown in Figure 1 to effectively separate laser heat load from the output facet, hence strongly reducing facet temperature even below the laser cavity temperature developed in our previous work [19,20]. In this work, we fabricated and carried out detailed characterization of the devices, studied their optimum working conditions, and revealed the elimination of COMD in LDs [21,22]. The LD waveguide is divided into two sections, laser and passive waveguide, which gives electrical and thermal isolation.…”
Section: Design and Measurement Methodsmentioning
confidence: 99%
“…We utilized the CMOS-based-thermoreflectance (TR) method (Figure 2) to obtain facet temperatures of LDs. It is a well-established surface temperature measurement method [25,26,27,28] and its principle is based on the relative change in reflectivity due to temperature change given as:…”
Section: Design and Measurement Methodsmentioning
confidence: 99%
“…В настоящее время активно развиваются методы, позволяющие увеличить предельную мощность лазерных диодов и их срок службы [1][2][3]. Одним из таких методов является пассивация поверхности излучающей грани полупроводниковых лазеров.…”
Section: Introductionunclassified
“…Along with the rapid development of fiber lasers, high power and PCE have become more critical to provide a cost-effective laser diode. To increase the output power [9,10] and power conversion efficiency [11], epitaxial design methods [12][13][14][15], epitaxial growth technologies [16,17], facet reliability against COMD [18][19][20][21], and passivation technologies [8,22,23] have been greatly improved. Increasing the reliable output power and PCE are always fundamental pursuits in research and practical applications.…”
Section: Introductionmentioning
confidence: 99%